If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 16) = 0 Reorder the terms: 6(16 + x) = 0 (16 * 6 + x * 6) = 0 (96 + 6x) = 0 Solving 96 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-96' to each side of the equation. 96 + -96 + 6x = 0 + -96 Combine like terms: 96 + -96 = 0 0 + 6x = 0 + -96 6x = 0 + -96 Combine like terms: 0 + -96 = -96 6x = -96 Divide each side by '6'. x = -16 Simplifying x = -16
| (5x+2)(5x+2)=144 | | X-8=-4-26 | | 7x-3x-50=20 | | y-2(y-3)+4= | | 2x+3x-5=50 | | 35z-11=59 | | x=6(2x+1) | | -4-6=5x+9-4x | | 0(8b+4)= | | 26R-3R^2=0 | | 11x+3=2x | | -75=-3x+3 | | 4x-9-9-8x= | | 5j-j= | | X+X+10+2(2X+10)=180 | | 8h-4h= | | -9t+3=-10t | | 2x-(4y-3)+5+-3+-1= | | -(4xy-10)+3(3xy+6)= | | 6+4r=5r | | 3-3*6-2=12 | | 18-r=-323 | | -15x-14= | | 4x-1=10x+8 | | 22+z=-180 | | Y=x+-5 | | 249=4x^2+32x-11 | | 8-d=d-6 | | 7+5j=6j | | Ax-y+z=6 | | -0.03x+0.11(x+16000)=2080 | | 5t+7r-15r= |